Alcohol mortality, drinking behaviour, and business cycles: Are slumps really dry seasons? - Edvard Johansson; Petri Böckerman; Ritva Prättälä; Antti Uutela (The Research Institute of the Finnish Economy (ETLA), 2005)
This paper explores the connection between alcohol mortality, drinking behaviour and macroeconomic fluctuations in Finland by using both aggregate and micro-level data during the past few decades. The results from the aggregate data reveal that an improvement in regional economic conditions measured by the employment-to-population rate produces a decrease in alcohol mortality. However, the great slump of the early 1990s is an exception to this pattern. During that particular episode, alcohol mortality did indeed decline, as there was an unprecedented collapse in economic activity. The results from the micro-data show that an increase in the employment-to-population rate and expansion in regional GDP produces an increase in alcohol consumption while having no effect on the probability of being a drinker. All in all, the Finnish evidence presented does not overwhelmingly support the conclusions reported for the USA, according to which temporary economic slowdowns are good for health. In contrast, at least alcohol mortality seems to increase in those bad times that are not exceptional economic crises like the one experienced in the early 1990s. However, there is evidence that alcohol consumption is strongly procyclical by its nature. This suggests that alcohol consumption and mortality may be delinked in the short-run business cycle context. – – As we will refer to these concepts in the text, we have included a short discussion on each of them.
Keywords: E32; I12; R11; 330; alcohol mortality; drinking; business cycles; Alkoholkonsum; Sterblichkeit; Konjunktur; Schätzung; Finnland